Improving women's experience during speculum examinations at routine gynaecological visits: randomised clinical trial. Issue 7560 (27th June 2006) - Seehusen, Dean A; Johnson, Dawn R; Earwood, J Scott; Sethuraman, Sankar N; Cornali, Jamie; Gillespie, Kelly; Doria, Maria; Farnell, Edwin; Lanham, Jason
Abstract: Objectives To determine if a standardised method of leg positioning without stirrups reduces the physical discomfort and sense of vulnerability and increases the sense of control among women undergoing speculum examination as part of a routine gynaecological examination. Design Randomised clinical trial. Setting Family medicine outpatient clinic. Patients 197 adult women undergoing routine gynaecological examination and cervical smear. Intervention Examination with or without stirrups. Main outcome measures Women's perceived levels of physical discomfort, sense of vulnerability, and sense of control during the examination, measured on 100 mm visual analogue scales. Results Women undergoing examination without stirrups had a reduction in mean sense of vulnerability from 23.6 to 13.1 (95% confidence interval of the difference - 16.6 to - 4.4). Mean physical discomfort was reduced from 30.4 to 17.2 (- 19.7 to - 6.8). There was no significant reduction in sense of loss of control. Conclusion Women should be able to have gynaecological examinations without using stirrups to reduce the stress associated with speculum examinations. Trial registration US Army Central Investigation Regulatory Office. Trial No DDEAMC 05-11.